Tingkat Pengetahuan Siswi SMA Muhammadiyah I Palangka Raya tentang Penyakit Kanker Payudara - Syahrida Dian Ardhany; Guntur Satrio Pratomo; Siti Jamilah (Jurnal Surya Medika (JSM), 2018)
Breast cancer is the number 2 cause of death in the world. The incidence of breast cancer is mostly in women. Student knowledge is expected to reduce the impact of breast cancer. The purpose of this study is to know the level of knowledge of Muhammadiyah I senior high school students of Palangka Raya about breast cancer. Methode of this research was the descriptive method by using a questionnaire. The results obtained from 48 female students the percentage of correct answer was 69.99%. It can be concluded the level of knowledge of Muhammadiyah I senior high school students of Palangka Raya included in the category enough knowledge.